The Axis Shift in Fines - Mehmet Alpertunga Avci (Maliye Çalışmaları Dergisi)
Pragmatically, legal and fiscal doctrines may diverge by achieving purposes and obtaining benefits with fines. However, the expectation is that fiscal purposes strengthen without preceding the legal ones. Otherwise, the capacity for fines to generate revenue may eclipse their functions to prevent, deter, and correct. In such a case, it becomes difficult to detain high income people for actions breaching the social order, belief in justice and equality erodes, deterrence of fines decreases, and the financial compliance of public debtors weaken. Therefore, a purposeoriented axis shift in fines complicates the act of protecting society frounlawful actions, detention from repetition by correction, and punishment as a warning or deterrent to others. This article propounds on the axis shift in fines from collectability and forecastability. It argues that primary purposes lag behind fiscal ones due to this shift toward the capacity of fines to generate revenue. This study supports the claim above by using the Central Government Budget Statistics of the General Directorate of Accounting for 2007-2020 to evaluate the doctrinal knowledge of current and data-based projection on fines. This study shows a dramatic and consistent decrease in collectability, despite the success in forecastability. Even the expected fiscal purposes are distant, with the axis shift eclipsing the primary objectives. Further research is needed to better understand the ways in which fines can enhance or generate fiscal and legal techniques.